The measurement of velocities of P and S waves in boreholes at Mizuho Station and Minami-Yamato Nunataks, East Antarctica - Ishizawa, Kenji; Mae, Shinji (1985)
P(論文) At Mizuho Station (70°42'S, 44°20'E) velocity profiles of P and S waves down to a depth of 208m were measured on 30 July and 1 August 1983,the waves were generated by hitting an iron block set on the snow surface and traveled waves were detected by geophones set in boreholes. It was revealed that the velocities of P and S waves continuously increased with depth. At Minami-Yamato Nunataks, velocities of both waves were obtained down to a depth of 100m in a bare ice region on 29 December 1983. The obtained velocities were constant from the surface to a depth of 100m, being 3.83km・s^<-1> for P wave and 2.01km・s^<-1> for S wave. P and S wave velocities at a depth of 100m at both sites were compared. It was found that the P wave velocity was almost the same at both sites, whereas the S wave velocity at Minami-Yamato Nunataks was larger than that at Mizuho Station, in spite of nearly identical ice density at both sites. The difference in the S wave velocity is discussed on the basis of difference in the crystal orientation. departmental bulletin paper